2009
DOI: 10.1128/mcb.00364-09
|View full text |Cite
|
Sign up to set email alerts
|

Fbxo45 Forms a Novel Ubiquitin Ligase Complex and Is Required for Neuronal Development

Abstract: Fbxo45 is an F-box protein that is restricted to the nervous system. Unlike other F-box proteins, Fbxo45 was found not to form an SCF complex as a result of an amino acid substitution in the consensus sequence for Cul1 binding. Proteomics analysis revealed that Fbxo45 specifically associates with PAM (protein associated with Myc), a RING finger-type ubiquitin ligase. Mice deficient in Fbxo45 were generated and found to die soon after birth as a result of respiratory distress. Fbxo45؊/؊ embryos show abnormal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
138
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(147 citation statements)
references
References 49 publications
8
138
1
Order By: Relevance
“…8 We confirmed that human Fbxo45 interacts with endogenous PAM and Skp1, but not with Cullin1 or Rbx1, by immunoprecipitation and western blotting (Supplementary Figure 1d). Yeast two-hybrid analyses revealed that Fbxo45 bound to Skp1 through the F-box domain, and PAM via the SPRY domain (Supplementary Figure 1e).…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…8 We confirmed that human Fbxo45 interacts with endogenous PAM and Skp1, but not with Cullin1 or Rbx1, by immunoprecipitation and western blotting (Supplementary Figure 1d). Yeast two-hybrid analyses revealed that Fbxo45 bound to Skp1 through the F-box domain, and PAM via the SPRY domain (Supplementary Figure 1e).…”
Section: Resultssupporting
confidence: 67%
“…[1][2][3][4][5][6] Previous studies have shown that in contrast to other F-box proteins that assemble SCF ubiquitin ligase complexes, Fbxo45 forms an atypical ubiquitin ligase complex that contains Skp1 and the Ring-finger protein PAM (protein-associated with myc) also known as MYCBP2 (mycbinding protein 2). 7,8 Fbxo45 has been linked to the proteasomal degradation of a few targets including p73 9 and Munc13-1. 10 Fbxo45 is one of only six F-box proteins that are conserved in metazoans and the only F-box protein known to contain a SPRY domain, 3 which was first identified as a sequence repeat in the dual-specificity kinase splA and ryanodine receptors.…”
mentioning
confidence: 99%
“…However, in the F-box protein family, Fbxo45 is the only member that contains a SPRY domain. Previous studies have indicated that Fbxo45 is involved in controlling synapse formation (3), neurotransmitter release (9), as well as neural differentiation (4,10). However, the molecular mechanisms leading to such diverse effects of Fbxo45 are complex and poorly understood.…”
mentioning
confidence: 99%
“…However, the molecular mechanisms leading to such diverse effects of Fbxo45 are complex and poorly understood. Both Fbxo45 and MYCBP2 knock-out mice exhibit perinatal lethality and display similar neurological defects suggesting that both molecules may functionally interact and play key roles in neuronal development (4,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation